DAMPAK PERATURAN VAKSINASI TERHADAP PEMILIHAN MODA PERJALANAN LUAR KOTA DI ACEH BARAT - Ferdiansyah Novriza; Roni Agusmaniza; Kusmira Agustian; Ary Firnanda (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2022)
AbstractThe ups and downs of the COVID-19 pandemic in Indonesia have caused economic, educational, and social aspects of public lives to experience a decline. Changes in community activity patterns are a warning for the central and regional government to bring public lives back to normal. Such effort can be seen in the government issuing policies regarding preventive measures to suppress the impact of the COVID-19 pandemic. One kind of such policy is the regulation of Domestic Travelers (PPDN). This policy certainly has positive and negative impacts on both the users and providers of transportation services. The purpose of this study is to see the impact of the regulations applied on the characteristics of service users in choosing the mode of transportation. The alternative modes of transportation used in this study are public, private and air transportation. The method used in this study is a quantitative descriptive method by distributing questionnaires to the target samples. The data were then processed and analyzed using a multinomial logit model approach through STATA 13 software to obtain the probability of each mode of transportation. The results show that there were several factors that influence the choice of transportation modes, the amount of income (X1), type of work (X4), gender (X3), cost (X2), travel time (X6) and comfort (X7). The probabilities of the three selected modes of transportation were Ppublic transportation = 56.07%, Pair freight = 34.54 % and Pprivate transport = 6.08%. The results indicate that the more demanding mode of transportation was the land transportation (public transportation).Keywords: Mode of Transportation, COVID-19, Logit Model, PPDN.